'What I said' versus 'what you heard': a comparison of physicians' and parents' reporting of anticipatory guidance on child safety issues. Issue 4 (December 1995) - Morrongiello, B. A.; Hillier, L.; Bass, M.
Abstract : OBJECTIVE: Unintentional injuries are the number one cause of death for infants. Many of these injuries could be prevented if parents took additional safety precautions. In this study physicians' and parents' perspectives regarding the part that physicians play in educating first time parents about child safety issues were compared. METHODS: All pediatricians and family physicians in London, Ontario were surveyed by mail (68% return rate) regarding their practices, attitudes, and beliefs related to parent education about child safety issues. A sample of 114 first time mothers, including 38 each with 6, 12, and 18 month old infants, completed a telephone interview. All parents had physicians who had returned questionnaires. RESULTS: There was good correspondence between parents' and physicians' judgments about the safety issues most often covered, and what role physicians should adopt regarding parent education about child safety issues. In addition, they both agreed that parents seldom seek out safety information by asking questions. Relative to parent reports, however, physicians significantly overestimated the time they spent on safety issues and the degree of their direct involvement in communicating this information. The best predictor of time spent by physicians on safety issues was their rating of the importance of assuming the role of parent educator. The best predictor of parents asking questions about child safety was their rating of the adequacy of physicians' responses to previously asked questions. CONCLUSIONS: The results suggest that both physicians and parents contribute to undermine communication about child safety during well-baby visits.